Transformasi Ekonomi Islam: Menggagas Nilai Zuhud dalam Sistem Ekonomi Spiritualitas - Mawardi, Imam; Su'eb, Muchammad; Afandi, Nihro (Journal of Islamic Economics Studies and Practices, 2023)
The purpose of the researcher in this article is to analyze the philosophical value of zuhud in Islamic economics in order to obtain justice, balance and simplicity in meeting the needs of life and pursuing their economic goals in a way that is in accordance with Islamic values. This research method is a descriptive analysis method, in this study using a type of descriptive qualitative research, the approach understands the philosophical value of zuhud in Islamic economics. While the data collection technique used by the author in this study is to review the review of articles and previous studies, books, websites and POP (Publish or Perish) applications as well as in other literature studies. The result of this research is that zuhud is very important in Islamic economics because it helps people to obtain justice and balance in meeting their needs. In Islamic economics, zuhud has several important philosophical values, including: First, the Value of Simplicity. Second, the value of justice. Third, the balance value. Fourth, the value of piety. In an economic context, zuhud helps people to pursue their economic goals in a way that is in accordance with Islamic values and provides benefits to society as a whole. According to Imam al-Ghazali, there are seven conditions that must be met by humans for the preservation of the concept of din (religion) in economic practice. First, is goodwill at the beginning of economic activity. Second, humans must meet the requirements of social utility, as in commerce. Third, economic activity should not deprive people of Islamic principles. Fourth, remembrance (remember) to Allah must be in the market. Fifth, humans do not have to be greedy. Sixth, regardless of legal opinion (fatwa) a Muslim must listen to his own voice in order to achieve resonance in trade along with Islamic principles. Seventh, is fair trade and conduct. One of the objectives of the teachings of the Qadiriyah Wan Naqsabandiyah Order is to develop human love (mahabbah) for Allah SWT.